From Sociology of Literature to Sociocriticism and SociologicalAesthetics - Pouliquen, Hélène (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This  paper proposesa brief tour through the main contributions of the principal theor ists who influenced the formation of fields of study in the horizons of Sociology of Literature and the different approaches of Sociocriticism, emphasizing on the breaking points between these disciplines and the developments brought about by them. Finally, a new development is introduced, which feeds from both: Sociological Aesthetics,asahorizonforliteraryresearchwhichunderstandsliteratureinrelationtothethreedimen-sions in which is rooted:language,the individual and the collective,with special attention to its a esthetic particularity.